Efficient method for large-scale preparation of two components H and I of Sg-6 saponins from whole seeds of wild soybean (Glycine soja Sieb. and Zucc.). Issue 14 (26th August 2016) - Itabashi, Mei; Tsukamoto, Chigen; Kurosaka, Ayaka; Krishnamurthy, Panneerselvam; Shin, Tai-Sun; Yang, Seung Hwan; Son, Eunho; Chung, Gyuhwa
ABSTRACT: New saponin components, Sg-6 saponins, have been recently reported from the seeds of wild soybean ( Glycine soja ) which may have specific health benefits. To evaluate the possible health benefits, a large amount of Sg-6 saponins are needed, but general group A acetyl saponins and new Sg-6 saponins are eluted in overlapping peaks by ordinal preparative high-performance liquid chromatography and/or open column methods. A new method is proposed in this report. This method includes (1) deacetylation of group A acetyl saponins in alkali condition with KOH, (2) precipitation of Sg-6 saponins in acid condition with HCl, (3) recovery of Sg-6 saponins with aqueous methanol from the precipitate, and (4) elution of Sg-6 saponins by preparative reverse-phase open column. With this method, from 450 g of wild soybean whole seed powder, about 1 g of Sg-6 saponins (mixture of six components) was clearly separated from other saponins with 61% recovery. GRAPHICAL ABSTRACT: